The response of steel plates subjected to close-in blast loads - N. S. A., Razak; Aizat, Alias (IOP Science, 2021)
Steel plates are commonly used for civil infrastructures and military vehicles. Since public awareness on the risk of explosion increase, extensive research is performed to improve the blast resistance of structures such as steel plates. This paper presents numerical investigations of the response of unstiffened and stiffened square steel plates subjected to close-in blast loads at different plate orientations. The numerical investigations were performed using finite element software ABAQUS. The target plates were subjected to blast loads produced by Plastic Explosive No.4 (PE4) with the mass range from 10 g to 20 g. The plates were stiffened with two stiffener configurations and in each configuration, the plate was tilted at three different angles of orientation, namely 0°, 15° and 45°. The results were compared against unstiffened square plates. The response of the plate was quantified in terms of the maximum central displacement of the plate. The results suggest tilted steel plates with the presence of stiffeners improves the blast resistance of the steel plates.